Erosion in centrifugal compressor impellers - Harris, P. K. (Cranfield University, 1996)
An experimental and theoretical study of erosion in centrifugal compressor impellers is presented. An experimental rig using laser anemometry techniques was employed to create a database of particle restitution ratios for a range of materials. This data was unique in that the particle rebound was measured in a quiescent condition where the aerodynamic effects had been minimised, and also parametric factors not previously available were included. These values were incorporated into the existing Particle Trajectory Code developed by Cranfield University and Rolls Royce PLC. The code is used to calculate the trajectories of discrete particles in three dimensional gas turbine geometries, and the ensuing erosion. It was modified to include the effects of the periodic boundary conditions, particle fragmentation, splitter blades, and variations in inlet dust concentration profile. Flowfield calculations were performed on a Rolls Royce GEM-2 and splittered GEM-60 impeller, which both represent the high pressure stage of the axial + centrifugal compression system of GEM engines. A procedure developed by Tourlidakis, for the analysis of steady viscous flow in high speed centrifugal compressors with tip leakage, was used to generate the flowfields. The GEM-2 impeller flowfield was analysed at 1009c speed, and validated with calculations and measurements which had been taken for previous projects. Simulated erosion data under the same conditions was checked using practical results obtained in a Rolls Royce PLC Helicopter Engine Environmental Protection Programme, and good agreement was achieved. In order to provide a qualitative, experimental assessment of erosion, a GEM-60 impeller was coated with four layers of paint of different colours. Two sizes of quartz particle, each at three different vane heights, were then seeded into the impeller while it was run cold at (the maximum) 70% speed. The erosion patterns generated compared well with the results generated by the Particle Trajectory Code.